ARTISTIC AND FUNCTIONAL ROLE OF ANTITHESIS IN THE ARCHITECTONICS OF THE NOVELLA "KAMINNIA PID KOSOIU" BY OLHA MAK - Kurinna, Nataliia; Bunyk, Tetiana (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2026)
The article investigates the functioning of antithesis in Olha Mak’s novella Kaminnia pid kosoiu (Stones Under the Scythe) as a key artistic device that ensures the depth and truthfulness of the Holodomor tragedy’s representation. It is established that antithesis in the work is implemented at various levels – from syntactic to conceptual-semantic – and performs emotional, structural, symbolic, and philosophical functions. Particular attention is paid to the analysis of contrasts between children’s and adults’ perceptions of the world, village and city, hope and despair, good and evil, mercy and cruelty, life and death, which form psychological tension, organize the plot, and shape its inherent symbolic dimension. The study employs a complex of general scientific and specialized methods: analysis and synthesis to generalize theoretical propositions; structural-semantic to study antithetical constructions; contextual analysis to interpret artistic images; the comparative method to contrast different types of oppositions; and elements of the hermeneutic approach for a deeper understanding of the text’s semantic levels. The scientific novelty of the research lies in the comprehensive conceptualization of antithesis as a leading principle of the artistic organization in Olha Mak’s Kaminnia pid kosoiu. This goes beyond its traditional interpretation as a stylistic figure and reveals it as a universal mechanism of artistic thinking and modeling of the Holodomor historical tragedy. The novelty is also driven by the consideration of the diasporic context of the author’s work, which allows for interpreting antithesis as a tool for preserving national memory, representing traumatic experience, and forming an alternative vision of historical events to the Soviet narrative. The practical significance lies in the possibility of using the research results in teaching Ukrainian literature (specifically the theme of the Holodomor), in preparing lectures and seminars, writing academic papers, as well as in further literary studies on the poetics of contrast.